Rare Co-Occurrence of Visual Snow in a Female Carrier With RPGRORF15-Associated Retinal Disorder - Tuekprakhon, Aekkachai; Pawestri, Aulia Rahmi; Suvannaboon, Ragkit; Thongyou, Ketwarin; Trinavarat, Adisak; Atchaneeyasakul, La-Ongsri (Frontiers in Genetics, 2021)
X-linked retinitis pigmentosa (XLRP), a rare form of retinitis pigmentosa (RP), is predominantly caused by mutations in the retinitis pigmentosa GTPase regulator (RPGR) gene. Affected males often present with severe phenotypes and early disease onset. In contrast, female carriers are usually asymptomatic or show stationary phenotypes. Herein, we reported an 8-year-old female carrier, a daughter of a confirmed RP father with RPGR mutation, with an early onset of progressive cone-rod pattern retinal dystrophy. Additionally, the carrier experienced visual snow-like symptom as long as she recalled. Ophthalmological examination showed the reduction of visual acuity and attenuation of photoreceptor functions since the age of 5 years. Further analysis revealed a heterozygous pathogenic variant of the RPGR gene and a random X-inactivation pattern. Although she harboured an identical RPGR variant as the father, there were phenotypic intrafamilial variations. The information on the variety of genotypic and phenotypic presentations in XLRP carriers is essential for further diagnosis, management, and monitoring of these cases, including the design of future gene therapy trials.